Honouring Seppo Koponen on the occasion of this 70th Birthday - Marusik, Yuri; Fet, Victor (Zootaxa, 2014)
Seppo Koponen was born in Turku, Finland, on November 2, 1944. After graduating from high school, Seppo was admitted to the University of Turku in 1963. He specialised in Ecology and Zoosystematics, and studied also Botany, Genetics, and Geography. He did his M.S. work (1969) on peat bog spiders, and his doctorate research (Phil. Lic. Thesis, 1978), on herbivorous insects living on birch trees in Lapland and Greenland.  Seppo’s mentor and supervisor in Arachnology was Pekka T. Lehtinen (see Marusik & Koponen 2014). While studying in the University of Turku, in the late 1960s Seppo worked as an assistant in the Department of Zoology. After his military service, Seppo was appointed a Curator in the Zoological Museum of the University of Turku in 1971, and continued to work there for 40 years, until his retirement in 2011.